Effect of nonthermal plasma treatment on the surface of dental resins immersed in artificial saliva - Santos, Daniela Micheline dos [UNESP]; Vechiato-Filho, Aljomar Jose [UNESP]; Pesqueira, Aldiéris Alves [UNESP]; Guiotti, Aimée Maria [UNESP]; Rangel, Elidiane Cipriano [UNESP]; Da Cruz, Nilson Cristino [UNESP]; Goiato, Marcelo Coelho [UNESP] (De Gruyter, 2016)
This study aimed (1) to use scanning electron microscopy associated with energy-dispersive spectroscopy (SEM-EDS) to characterize the surface of dental resins after nonthermal plasma (NTP) treatment and (2) to use surface energy analysis to evaluate whether NTP treatment protects the microhardness of the resins against the degradative effects of saliva. Twenty-eight acrylic and composite resin discs were fabricated and divided into four groups. Two groups received no surface treatment [control acrylic resin (Co/AR) and control composite resin (Co/CR] and two groups [NTP-treated acrylic resin (NTP/AR) and NTP-treated composite resin (NTP/CR)] were treated with NTP. One disc from each group was analyzed using SEM-EDS. Ten discs were subjected to surface energy analysis (before and after NTP) and microhardness assessments (at various time points). p<0.05 was used to determine statistical significance. Surface energy decreased after NTP treatment. Microhardness was reduced after 30 days in the Co/AR group and between 15 and 30 days in the NTP/AR group. Microhardness decreased in the Co/CR group after 15 and 30 days, whereas there was no difference after 30 days in the NTP/CR group. SEM images showed the presence of cracks and holes after 30 days in both Co/AR and NTP/AR groups. Cracks and silicon particles were observed after 30 days in the Co/CR group. Both the acrylic and composite resins exhibited hydrophobic properties after NTP treatment. The reduction in microhardness of the acrylic resin after NTP treatment was lower than that of the composite resin.
Keywords: acrylic resin; composite resin; microhardness; plasma gases; surface energy